Vandringer i mørket: Hvad man ser når solen ikke forstyrrer - Grøn, Rasmus (Academic Quarter | Akademisk kvarter, 2019)
This article explores the visual experience of walking in darkness. Based primarily on phenomenological theories and analyses of walking and/or darkness, the topic is analyzed in relation to a guided night tour in a dark resort in Denmark. The tour is described as an experiential oscillation between moments of ‘antagonistic darkness’, blocking the human vision, and ‘symbiotic darkness’, opening up alternative visual perceptions of the world. These ways of looking are labeled as, respectively, distorted, transformative and sublime. The experiental fluctuation of the tour is ascribed to the contextual and temporal aspects of walking and standing as well as the specific staging of the walking tour as event.